Preciseness in Details -- Analysis of Several Common Mistakes in Foundations of mathematics Problems - Bo, Huang (Journal of Education and Educational Technologies, 2023)
Teaching quality monitoring has always been a focus and difficulty in college teaching management, as well as the weakest link in the process of cooperative school-running. The lack of process monitoring has seriously affected the overall improvement in the quality of cooperative school-running. Based on the author’s own practice and research accumulation in teaching quality monitoring, the paper draws lessons from international experience, seeks enlightenment from multiple theories, finds problem orientation by sorting the key elements that affect cooperative school-running, and builds an overall teaching quality monitoring system suitable for cooperative school-running by higher vocational colleges, local government and schools. The system is constantly enriched and improved through school-based practice, with a view to opening up new paths and providing new thinking for domestic colleges to create a new pattern of cooperative school-running. Objective: To observe the clinical efficacy of Bufei Decoctions in the treatment of pulmonary Pseudomonas aeruginosa multiple drug-resistant bacterial infections in patients with PVS. Methods: 61 patients were randomly divided into Chinese medicine group (29 cases) and control group (32 cases). The control group selected antibiotics and rehabilitation routine treatment according to sputum culture susceptibility test. The traditional Chinese medicine group was given "Bufei Decoctions" on the basis of the control group. The curative effect and adverse reactions were observed. The course of treatment was 14 days. Result: After 14 days of treatments, the improvement time of clinical symptoms, serum WBC and CRP levels in the Chinese medicine group were significantly lower than those in the control group (P< 0.05), and the effective rate and the release rate of multi-drug-resistant bacteria in the Chinese medicine group were higher than those in the control group (P < 0.05). Conclusion: Bufei Decoctions is superior to conventional antibiotics in the treatment of pulmonary Pseudomonas aeruginosa multi-drug-resistant bacterial infections in patients with PVS.